Prediction of a native ferroelectric metal - Alessio Filippetti (Nature Portfolio, 2016)
Ferroelectricity, spontaneous switchable polarization, is usually deemed incompatible with the electronic screening of a metal. Here, the authors use ab initio theory to predict that metallicity natively coexists with ferroelectric polarization and finite depolarizing fields in the perovskite Bi5Ti5O17.